Does Temporary Employment undermine the Quality of Permanent Jobs? - Chiara Pollio; Fabio Landini; Elena Prodi; Alessandro Arrighetti (Global Labor Organization (GLO), 2023)
Standard screening and core-periphery theories claim that temporary employment does not undermine the quality of permanent jobs. In contrast, organizational approaches suggest that firms use temporary contracts to pursue low-road employment strategies, which involve the creation of cheap and low quality jobs also for permanent employees. We test these predictions by matching administrative data at the occupation, worker and firm level from the Emilia Romagna region (Italy). Job quality is measured through non-wage occupation-specific factors capturing self-realisation, recognition and social support. Baseline and IV estimates show that a larger use of temporary employees is associated with permanent jobs of lower quality. Moreover, in firms using more temporary workers the jobs of permanent employees are more routinized and less complex. Also, in such firms, permanent workers hold occupations that receive less training and involve less teamwork. These results suggest that where temporary work is used, the low quality of permanent positions is driven by work arrangements that tend to economize on individual skills and competences, which is consistent with the low-road employment hypothesis. Related managerial and policy implications are discussed.
Keywords: D22; J28; J41; L23; 330; job quality; temporary employment; skills; labour market institutions